Dampak Toxic Parenting pada Kesehatan Mental Remaja Akhir di Tangerang Selatan - Yunita Choiriah; Wa Ode Asmawati (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study investigates the impact of toxic parenting on the mental health of late adolescents in Benda Baru, South Tangerang. The background of this research is rooted in the increasing number of adolescent mental health issues linked to unhealthy parenting practices, including excessive control, verbal abuse, physical violence, criticism, and neglect. The study aims to analyze the underlying causes of toxic parenting from the perspectives of adolescents, parents, and other family members, as well as to identify its psychological, social, and behavioral consequences. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and documentation involving late adolescents aged 18–22, their parents, siblings, and key community informants. The findings indicate that toxic parenting often originates from intergenerational trauma, unresolved stress, and socio-cultural pressures, leading parents to adopt coercive and destructive parenting strategies. These practices contribute to significant mental health problems among adolescents, including anxiety, depression, low self-esteem, difficulties in social adaptation, and tendencies toward self-harm. The study underscores the importance of preventive efforts through parenting education, psychosocial support at the community level, and the development of youth-friendly mental health services. The implications suggest that multi-sector collaboration involving families, schools, community leaders, and local government is essential to create a supportive environment that can break the cycle of toxic parenting and promote adolescent well-being.